Bitwa pod Zurychem i pod Bernem. Szwajcarski epizod Aleksandra Wata. Dyptyk - Zieliński, Jan (Colloquia Litteraria, 2012)
The Battle of Zurich and Berne. Swiss episode of Aleksander Wat. Diptych Aleksander Wat’s participation in the international congress of Pen Clubs in Zurich in June 1947, was for him an opportunity not only to reflect on his continuing role in journalism and cultural life in post-war Poland (among others indirectly influenced the decision to leave Poland permanently in 1963), but also to see the Cathedral of St. Vincent of Zaragoza in Bern and its famous stained glass window, depicting the mystical mill. A similar theme – the mill appears in the poem Condemned which the author interprets in multiple contexts: historical, biblical (the book of Samuel), literary (Gałczyński, Schulz, Dürrenmatt), painting (including Breughel, Schiele), film (Kondratiuk), and others. This interpretation also leads to a broader view of the importance of the theme (and symbol), which is in literature and art a mill in general.